การจัดการความรู้เรื่องการผลิตข้าวของเกษตรกร ตำบลเหมืองแก้ว อำเภอแม่ริม จังหวัดเชียงใหม่ - วินัย ขาวมี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Independent Study Title “Knowledge Management of Farmers on Rice Production at Mueang Kaew Sub-district, Mae Rim District, Chiang Mai Province” has objective to find out the Knowledge Management of Farmers on Rice Production at Mueang Kaew Sub-district, Mae Rim District, Chiang Mai Province. The purpose of the study were to investigate on the knowledge management, the problems and the suggestions on Rice production of agriculturists in the area of study. The participants were 134 farmers from Mueang Kaew Sub-district, Mae Rim District, Chiang Mai Province. The subject will be analysed on the method of knowledge management of farmers included creating, researching, developing and exchanging knowledges. The research found that knowledge management of farmers on rice production Includes the creation of knowledge and this knowledge construction by bringing the wisdom passed down from ancient to practice, combined with the knowledge which transfer of the agricultural extension officers as well as the knowledge gained from a neighbor applied in the farm. The pursuit of knowledge found that the farmers who participate in activities such as training as well as medias like television, radio, document, applied knowledge reveal that the knowledge derived from practice. The exchanged knowledge isshared in discussion after work in the community such as markets, shops and facilities within the community. The findings showed that the problems and difficulties are the deficiency of effective rice manufacturing, new training methods and belief on traditional ways. Therefore, the rice production have not been developing as expected. The direction of this paper is the government and relative organization should support the development of rice manufacture, improve and exchange new knowledges in the communities.